2021
DOI: 10.1117/1.oe.60.10.103101
|View full text |Cite
|
Sign up to set email alerts
|

Kaczmarz holography: holographic projection in the Fraunhofer region

Abstract: The Kaczmarz algorithm is an iterative method for solving linear equations in the form of Ax = b. It is widely used in computed tomography (CT) and digital signal processing (DSP) but has yet to be adopted in computer-generated holography (CGH). Phase retrieval algorithms such as Gerchberg-Saxton or Fienup are significantly more popular in this field, however, in this paper we propose a unique and alternative approach to projecting a replay field through Discrete Fourier Transform (DFT) matrices and have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…From the work previously conducted on Kaczmarz holographic projections [12], it is noticeable the image quality for Kaczmarz outperforms Gerchberg-Saxton in 10 iterations. However, the main drawbacks of implementing Kaczmarz are its slow running time and ability to solely be adopted on smaller images 128x128 pixels since it relies on discrete Fourier transform (DFT) matrices.…”
Section: Algorithm Replay Field Image Qualitymentioning
confidence: 96%
See 4 more Smart Citations
“…From the work previously conducted on Kaczmarz holographic projections [12], it is noticeable the image quality for Kaczmarz outperforms Gerchberg-Saxton in 10 iterations. However, the main drawbacks of implementing Kaczmarz are its slow running time and ability to solely be adopted on smaller images 128x128 pixels since it relies on discrete Fourier transform (DFT) matrices.…”
Section: Algorithm Replay Field Image Qualitymentioning
confidence: 96%
“…Our earlier investigation, on Kaczmarz holographic projections in the Fraunhofer region [12] revealed that while very high quality replay fields are generated, it is still comparatively slower than the more widely used Gerchberg-Saxton. The Kaczmarz algorithm iterates the Ax component in a linear equation on a row-by-row basis and therefore explains the slower running of this phase retrieval method.…”
Section: Fig 1 Diffraction and Replay Fields Coordinate Systemmentioning
confidence: 99%
See 3 more Smart Citations